2011
DOI: 10.4049/jimmunol.1100378
|View full text |Cite
|
Sign up to set email alerts
|

Functional Gap Junctions Accumulate at the Immunological Synapse and Contribute to T Cell Activation

Abstract: Gap junction (GJ) mediate intercellular communication through linked hemichannels from each of two adjacent cells. Using human and mouse models we show that connexin 43 (Cx43), the main GJ protein in the immune system, was recruited to the immunological synapse during T cell priming as both GJs and stand-alone hemichannels. Cx43 accumulation at the synapse was antigen-specific and time-dependent, and required an intact actin cytoskeleton. Fluorescence recovery after photobleaching and Cx43-specific inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 45 publications
3
84
1
Order By: Relevance
“…Recently, we showed that Cx43 accumulates at the immunological synapse (IS) during Ag-specific CD4 + T cell priming, mediating bidirectional crosstalk between DCs and T cells. We demonstrated that Cx43-GJIC between DCs and T cells regulates Ca 2+ signals and T cell activation (14), pointing to a role for Cx43 as an important functional component for intercellular signaling in the immune system.…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…Recently, we showed that Cx43 accumulates at the immunological synapse (IS) during Ag-specific CD4 + T cell priming, mediating bidirectional crosstalk between DCs and T cells. We demonstrated that Cx43-GJIC between DCs and T cells regulates Ca 2+ signals and T cell activation (14), pointing to a role for Cx43 as an important functional component for intercellular signaling in the immune system.…”
mentioning
confidence: 85%
“…Previously, we demonstrated that Cx43 accumulates in the IS during DC-mediated priming of CD4 + T cells, promoting lymphocyte activation through the formation of functional GJs and increased intracellular Ca 2+ signaling in T cells (14). Given that the reciprocal activation of DCs and NK cells is a cell contact-dependent process and shares some mechanisms with the DC-mediated T cell priming such as the formation of a functional IS (18), we aimed to examine whether Cx43-GJ channels may be involved in DC-NK intercellular communication.…”
Section: Nk Cells and Dcs Communicate Through Functional Cx43-mediatementioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, connexins regulate many physiological processes. Cx43 is the most common connexin isoform and is expressed by many different cell types, including gastric and intestinal epithelial cells (49)(50)(51), ventricular myocytes, astrocytes, muscle cells, endothelial cells (52)(53)(54), and several types of immune cells (including T and B cells, neutrophils, mast cells, monocytes, and macrophages) (55)(56)(57)(58)(59)(60). We report that Cx43 is produced by AZ-521 cells but not by several other cell types that are commonly used for studies of VacA and provide evidence that variation among cell types in susceptibility to VacA-induced cell death is attributable at least in part to cell type-specific differences in Cx43 protein production.…”
mentioning
confidence: 99%